Pengaruh Kepemimpinan, Motivasi Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. Kurnia Berdikari Sejahtera - Della Widya Ayu; Milda Handayani; Rini Wijayaningsih (Universitas 45 Surabaya, 2024)
The Influence of Leadership, Work Motivation and Workload on Employee Performance at PT. Kurnia Berdikari Sejahtera. This research aims to find out how much influence Leadership, Work Motivation and Workload have on Employee Performance which has an impact on PT. Kurnia Berdikari Sejahtera. This type of research is quantitative. The population in this study were all employees of PT. Kurnia Berdikari Sejahtera, located in Bekasi City. The sampling technique uses Probability Sampling (Simple Random Sampling). Data were collected through distributing questionnaires directly and via google form to 110 respondents, with data processing using SPSS version 27. Data that met the requirements was obtained using validity and reliability tests and classical assumption tests. The data analysis techniques used are multiple linear regression analysis, t statistical test (partial), F test (simultaneous) and coefficient of determination test (R²). Based on the results of this research, it is stated that leadership, work motivation and workload simultaneously have a significant effect on the performance of PT employees. Kurnia Berdikari Sejahtera. And the Leadership variable partially has a positive and significant influence on employee performance variables, the Work Motivation variable partially has a positive and significant influence on employee performance and the Workload variable has a positive and significant influence on employee performance. Based on this, it can be concluded that it is proven that leadership, work motivation and workload have a positive influence on employee performance. Each level of leadership, work motivation and workload has a very important role in employee performance results.